House of stairs. - Sleator, William (New York : Dutton, 1974)
Five fifteen-year-old orphans of widely varying personality characteristics are involuntarily placed in a house of endless stairs as subjects for a psychological experiment on conditioned human response.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
6.0
6.0
5-8.
Keywords: Science fiction; Science fiction